2019
DOI: 10.1002/clc.23141
|View full text |Cite
|
Sign up to set email alerts
|

Development of an entirely remote, non‐physician led hypertension management program

Abstract: Background Hypertension remains poorly controlled on the population level. National rates of control, even when defined leniently by BP < 140/90 mm Hg, are only ~50%. As growing healthcare costs coincide with tighter blood pressure (BP) targets, innovative management programs are needed to maximize efficiency of care delivery and optimize control. Hypothesis We aimed to develop a remote, navigator‐led hypertension innovation program that would leverage algorithmic care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…However, data supporting the use of RPM have so far been mixed, with variable results depending on condition and implementation. 16,[20][21][22][23][24][25][26] As COVID-19 cases began to emerge in our region, we identified a need for managing an increasing number of patients admitted to the hospital with COVID-19 in the setting of unparalleled resource constraints. We therefore rapidly designed and deployed an RPM program so that we could monitor and manage patients after discharge in their home environment using pulse oximeters, thermometers, and an app-based symptom assessment tool, monitored by a team of nurses.…”
Section: Background and Significancementioning
confidence: 99%
“…However, data supporting the use of RPM have so far been mixed, with variable results depending on condition and implementation. 16,[20][21][22][23][24][25][26] As COVID-19 cases began to emerge in our region, we identified a need for managing an increasing number of patients admitted to the hospital with COVID-19 in the setting of unparalleled resource constraints. We therefore rapidly designed and deployed an RPM program so that we could monitor and manage patients after discharge in their home environment using pulse oximeters, thermometers, and an app-based symptom assessment tool, monitored by a team of nurses.…”
Section: Background and Significancementioning
confidence: 99%
“… 32 Other studies found onboarding sessions, patient instruction manuals, and other device-support materials given to patients before participating in PGHD integration activities to be critical. Fisher et al 33 described a program with sustainable scalability that used nonlicensed patient navigators to provide patient-facing education.…”
Section: Resultsmentioning
confidence: 99%
“… 41 Setup time with patients added 45–60 min to a scheduled visit according to another article, and in others, time was needed to develop customized flowsheets, create patient registries, and identify relevant evidence for the use of PGHD in clinical care. 33 , 35 , 36 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…The models can also identify patients without previous complication events. Stratification of care management resources could include identifying candidates for remote monitoring programs at home [33, 34], and designating outreach resources ranging from digital strategies to personalized contact with a population health consultant, an engagement specialist, or a clinician. In this way, leveraging these predicative models can help improve the financial and health outcomes impact of care management.…”
Section: Discussionmentioning
confidence: 99%